Characterization of β-lactoglobulin gels induced by high pressure processing. (June 2018) - Li, Xiaoying; Mao, Like; He, Xiaoye; Ma, Peihua; Gao, Yanxiang; Yuan, Fang
Abstract: High pressure processing (HPP) is a non-thermal technology and has been widely used in the food industry. β‑lactoglobulin (β-Lg) is a globular protein and susceptible to pressure. This study investigated the properties of β-Lg gels induced directly by HPP (0.1–600 MPa for 30 min, 25 °C) with different protein concentrations at different pH. Results showed that the lowest protein concentration required to form β-Lg gels was 20% (w/v) at 400 MPa for 30 min at pH 3.0, 5.0 and 7.0, while 14% (w/v) protein was required to form gels at 600 MPa. The gel strength and textural properties increased with the increase of protein concentration and pressure, the gel formed at pH 5.0 had the highest strength. Raman spectra suggested that the content of α-helix decreased and random coil increased of β-Lg in gels with the increase of pressure. β-Lg gels formed more regular and stable network under 600 MPa than that under 400 MPa. Industrial relevance: In recent years, high pressure processing (HPP) has been used in the food industry as an innovative technology to improve gel properties of various kinds of proteins, including β‑lactoglobulin, casein, soy protein isolate, surimi, mytolin and so on. It was found that HPP could change the structure of protein, which could cause protein denaturation and aggregation and three-dimensional network structures were formed through disulfide bonds, electrostatic interactions, hydrophobic interaction, hydrogen bonds and others. β‑lactoglobulin is the main component of whey protein, which has been widely used in the food industry as gelling agents. β‑lactoglobulin gels could be used as a wall material and applied to the delivery system of functional components such as riboflavin. The objective of the current study was to investigate the properties of β-Lg gels formed through HPP directly, focusing on the effects of pressure, protein concentration and pH on the rheological properties, texture profile, protein secondary structure and microstructure of β-Lg gels. Highlights: β-Lg can form gels induced by HPP treatment directly ( P  ≥ 400 MPa for 30 min). HPP can improve rheological and textural properties of β-Lg gels. Gel strength of β-Lg gels reached the highest level at pH 5.0. Raman spectra showed that the content of α-helix decreased and random coil increased.